2015
DOI: 10.1155/2015/678924
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum LDL Cholesterol and Genetic Variation in Chromosomal Locus 1p13.3 among Coronary Artery Disease Patients

Abstract: Background. Several polymorphisms of a locus on chromosome 1p13.3 have a significant effect on low-density lipoprotein cholesterol (LDL-C), atherosclerosis, and acute coronary syndrome (ACS). Methods. We aimed to investigate the association between rs599839, rs646776, and rs4970834 of locus 1p13.3 and serum LDL-C and severity of coronary artery stenosis in ACS patients. Genotyping of the rs599839, rs646776, and rs4970834 polymorphisms was performed on Arab patients undergoing coronary angiography for ACS. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Besides, the minor allele G has been associated with a protective effect against the risk of CAD (OR = 0.422, 95% CI: 0.181–0.981) and lower levels of total cholesterol and LDLc in Indians [ 22 ]. Also, it was found to reduce the risk of stenosis in Arab CAD patients (OR = 0.51, 95% CI: 0.30–0.92) [ 23 ], and to lower serum LDLc levels in Japanese (OR = 0.7, 95% CI: 0.57–0.85) [ 24 ]. This rs599839 polymorphism is located on the 1p13.3 chromosomal region near the SORT1 (sortilin-1) gene, which encodes the VPS10P domain-sorting receptors involved in intracellular protein trafficking and the modulation of hepatic very-low-density protein secretion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the minor allele G has been associated with a protective effect against the risk of CAD (OR = 0.422, 95% CI: 0.181–0.981) and lower levels of total cholesterol and LDLc in Indians [ 22 ]. Also, it was found to reduce the risk of stenosis in Arab CAD patients (OR = 0.51, 95% CI: 0.30–0.92) [ 23 ], and to lower serum LDLc levels in Japanese (OR = 0.7, 95% CI: 0.57–0.85) [ 24 ]. This rs599839 polymorphism is located on the 1p13.3 chromosomal region near the SORT1 (sortilin-1) gene, which encodes the VPS10P domain-sorting receptors involved in intracellular protein trafficking and the modulation of hepatic very-low-density protein secretion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high level of high-density lipoprotein cholesterol (HDL-C) could induce reverse cholesterol transport and improve endothelial function, which decreases the risk of atherosclerosis [6], whereas a high level of low-density lipoprotein cholesterol (LDL-C) exerts effects on atherosclerosis [7]. Previous epidemiological studies that evaluated the blood lipids in AMD have not yielded similar relationships, and some studies have shown inverse relationships between these lipid levels and AMD risk [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, they found an association between this SNP and a decrease in LDL-C levels, such a finding possibly due to gene-gene interaction especially since the PSRC1, CELSR2, and SORT1 genes are found in a highly linked disequilibrium. 6 (Samani et al, Zhou et al, and Musunuru et al,) found that expression of a minor protective allele of rs646776 in the human liver was associated with an increase in hepatic expression of CELSR2, PRSC1, and SORT1 genes which correlated…”
Section: Discussionmentioning
confidence: 99%
“…40-50% of CAD risk is attributable to non-modifiable hereditary factors. 5,6 Recent GWAS have identified several genetic risk factors to be associated with CAD, including mutations in PSRC1, CELSR2, SORT1 genes on chromosome 1p13.3. 4,7 Since then, several studies have linked polymorphisms in these candidate genes to the development of CAD through their effect on hypercholesteremia and elevated levels of circulating LDL-C, known contributors to atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%